2021
DOI: 10.3390/s21155230
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Non-Interferometry Based Surface Plasmon Resonance Microscopes

Abstract: Surface plasmon microscopy has been of interest to the science and engineering community and has been utilized in broad aspects of applications and studies, including biochemical sensing and biomolecular binding kinetics. The benefits of surface plasmon microscopy include label-free detection, high sensitivity, and quantitative measurements. Here, a theoretical framework to analyze and compare several non-interferometric surface plasmon microscopes is proposed. The scope of the study is to (1) identify the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The surface plasmon resonance increases the probability of electron collision on the surface of AgNWs. When electrons jump from the Fermi energy level to the higher energy level, superhot electrons are generated due to thermal motion, and the energy captured by the surface plasma is released through electron–phonon scattering, which intensifies the oscillation of the surface plasma, that is, thermal energy. , The thermal energy is then transported to the external environment through the relaxation generated during the phonon–phonon vibration. Figure S4b–f in the Supporting Information shows the simulation with the same method at different cross-sectional depths as shown in Figure S4a, and the similar results could be confirmed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface plasmon resonance increases the probability of electron collision on the surface of AgNWs. When electrons jump from the Fermi energy level to the higher energy level, superhot electrons are generated due to thermal motion, and the energy captured by the surface plasma is released through electron–phonon scattering, which intensifies the oscillation of the surface plasma, that is, thermal energy. , The thermal energy is then transported to the external environment through the relaxation generated during the phonon–phonon vibration. Figure S4b–f in the Supporting Information shows the simulation with the same method at different cross-sectional depths as shown in Figure S4a, and the similar results could be confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…While it has been shown that the photothermal conversion layer could greatly improve performance of energy storage devices, photothermal conversion efficiency would be affected by surface morphology of conversion layer materials. Therefore, the theoretical simulation of the effect of surface morphology on photothermal conversion efficiency at −20 °C under one sun illumination is carried out and shown in Figure . , Five different surface morphologies are investigated as shown in Figure a–e. The results indicate that the cone spine surface with the largest specific surface area has the highest surface temperature.…”
Section: Resultsmentioning
confidence: 99%